PENGEMBANGAN PRODUK RED CASSAVA OMBRE CAKE TERHADAP TINGKAT PENERIMAAN MASYARAKAT - Christiana Mayang; Lina Mufidah; Eka Rachmawati (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2021)
The purpose of this research is: (1) Finding recipes of Red Cassava Ombre Cake products, (2) Knowing the level of public acceptance of Red Cassava Ombre Cake. This type of research uses 4D model R&D research (define, design, develop, and dissemination). With the stages (1) Define is the stage of setting and defining the terms of development, namely looking for 3 recipes reference of products Red Cassava Ombre Cake from 3 different sources, (2) Design is the stage of designing recipe development, namely designing recipes product development to be substituted with mocap flour in accordance with their respective criteria, the product developed is Red Cassava Ombre Cake, (3) Develop is the stage of product development and feasibility of product design to know the consumer's acceptability to the developed product, namely getting the right recipe from red cassava ombre cake product (4) Disseminate is the stage of implementing the revised product at the development stage on the real target, namely the product stage that has been tested through validation I, and validation II, and the test panellists of 30 panellists were then exhibited and tested through 50 panellists. The results of the study obtained: (1) The right recipe in the manufacture of Red Cassava Ombre Cake by using the main ingredients of flour 100% mocaf by packaged using plastic mica labeled. (2) The right recipe in the manufacture of Red Cassava Ombre Cake with the main ingredients mocaf flour that is packed with interesting and decorated with interesting anyway. (3) Data analysis techniques with product acceptance test show the results of public acceptance of Red Cassava Ombre Cake products with an average color of 3.46; aroma 3.48; texture 3.42; 3.50 sense favored by the public